Commercially Viable Hybrid Li-Ion/Metal Batteries with High Energy Density Realized by Symbiotic Anode and Prelithiated Cathode - Lin, Kui; Xu, Xiaofu; Qin, Xianying; Liu, Ming; Zhao, Liang; Yang, Zijin; Liu, Qi; Ye, Yonghuang; Chen, Guohua; Kang, Feiyu; Li, Baohua (Nano-Micro Letters, 2022)
The energy density of commercial lithium (Li) ion batteries with graphite anode is reaching the limit. It is believed that directly utilizing Li metal as anode without a host could enhance the battery’s energy density to the maximum extent. However, the poor reversibility and infinite volume change of Li metal hinder the realistic implementation of Li metal in battery community. Herein, a commercially viable hybrid Li-ion/metal battery is realized by a coordinated strategy of symbiotic anode and prelithiated cathode. To be specific, a scalable template-removal method is developed to fabricate the porous graphite layer (PGL), which acts as a symbiotic host for Li ion intercalation and subsequent Li metal deposition due to the enhanced lithiophilicity and sufficient ion-conducting pathways. A continuous dissolution-deintercalation mechanism during delithiation process further ensures the elimination of dead Li. As a result, when the excess plating Li reaches 30%, the PGL could deliver an ultrahigh average Coulombic efficiency of 99.5% for 180 cycles with a capacity of 2.48 mAh cm−2 in traditional carbonate electrolyte. Meanwhile, an air-stable recrystallized lithium oxalate with high specific capacity (514.3 mAh g−1) and moderate operating potential (4.7–5.0 V) is introduced as a sacrificial cathode to compensate the initial loss and provide Li source for subsequent cycles. Based on the prelithiated cathode and initial Li-free symbiotic anode, under a practical-level 3 mAh capacity, the assembled hybrid Li-ion/metal full cell with a P/N ratio (capacity ratio of LiNi0.8Co0.1Mn0.1O2 to graphite) of 1.3 exhibits significantly improved capacity retention after 300 cycles, indicating its great potential for high-energy-density Li batteries. Highlights: 1 A symbiotic host of porous graphite layer is designed as hybrid Li anode for Li ion intercalation and subsequent uniform plating. 2 An ultrahigh plating reversibility of 99.5% is achieved in the carbonate electrolyte. 3 An air-stable cathode prelithiation agent is introduced to provide extra Li source, resulting high energy density of the as-developed practical hybrid Li-ion/metal full cell.